A Decade of Police Use of Deadly Force Research (2011–2020). Issue 1 (February 2023) - Oramas Mora, Daniela; Terrill, William; Foster, Jacob
The current study provides findings from a systematic review of the police use of deadly force literature over the most recently completed decade (2011–2020). After an exhaustive search of four scientific databases, 1, 190 peer-reviewed articles related to the use of force were identified. Of these, 181 articles specifically examined deadly force, with 86 of them drawing on such force as the dependent variable. We found that the number of articles examining police use of deadly force increased dramatically over the course of the study period and encompassed a wide range of determinants of behavior. Citizen possession of a weapon continues to be the most consistent risk factor of police use of deadly force across decades of policing literature. Additionally, while many studies have attempted to examine the link between race and lethal force, a determination of such a relationship is difficult given both mixed findings and a lack of available national data.